Assessment of agricultural sustainability: Case study of Baltic States - Dalia Štreimikienė; Asta Mikalauskiene (Contemporary Economics, 2023)
The agri-food sector is the world's largest economic sector having the biggest impact on environment. According to the Food and Agriculture Organization of the United Nations (FAO), sustainable agriculture must meet the needs of present and future generations while ensuring profitability, environmental health and social and economic equity. Therefore, agricultural systems need transition to become more sustainable. The use of renewables in agriculture allows to reduce energy costs and GHG emissions and implement cyclic economy principles. Sustainability assessment of agriculture can be done by applying various sets of indicators. The sustainability assessment of agriculture can be performed on country and micro level. The paper presents assessment of agricultural sustainability of Baltic States based on indicators framework and applies MCDA tool for ranking of Baltic States in terms of agriculture sustainability.
Keywords: H30; P18; Q20; Q30; 330; sustainability; agriculture; MCDA; Baltic States